INSIGHTS INTO THE MONOMERS AND SINGLE DRUGS OF CHINESE HERBAL MEDICINE ON MYOCARDIAL PRESERVATION - Yuan, Shi-Min; Jing, Hua (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Chinese herbal drugs have been proved to be effective agents in myocardial protection by preventing ischemia-reperfusion injury. The underlying mechanisms as to how these agents work were however poorly elucidated. Studies on the monomers or on the single drugs have highlighted the possible rationales, leading to a better understanding of the pharmaceutical effects of the active parts of the herbs. These agents have been found to be structure-sensitive while they play the role of a protective ingredient. Polysaccharides of Chinese herbal medicine have pharmaceutical effects in immune modulation, anti-inflammation, anti-virus, anti-tumor, anti-aging mechanisms, with an anti-oxidative effect being a commonly recognized mechanism. Saponins are prone to alleviate calcium overload. As bioflavonoids commonly contain active phenolic hydroxy group, they have good anti-oxidant property. Those containing effective lignanoids and essential oils can result in a reduced nitric oxide secretion of the endothelial cells and an increased intercellular cell adhesion molecule-1 expression. Alkaloids may resist free radical injuries. Most importantly, modern in-depth research revealed that myocardial infarction is typically associated with apoptosis, and herbal medicine containing carbohydrates and glycosides showed cardioprotective effects by way of inhibiting apoptosis of myocytes. As a supplement to cardioplegia, some Chinese herbal drugs have become especially valuable in myocardial protection in open heart surgery by preserving metabolic energy. In conclusion, the classification of Chinese herbal medicine made according to their main active ingredients has facilitated the expression of their functioning mechanisms. Chinese herbal drugs play an important role in cardioprotection via many different mechanisms, the most recent and important finding being the inhibition of apoptosis.